2021
DOI: 10.1021/acs.chemmater.0c04839
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Transition-Enhanced Thermoelectric Transport in Rickardite Mineral Cu3–xTe2

Abstract: The binary copper chalcogenides Cu 2−δ X (X = S, Se, and Te) have recently gained significant interest due to their high thermoelectric performance at moderate temperatures. In an effort to unveil new Cu-based compounds with promising thermoelectric potential, Cu 3−x Te 2 rickardite mineral emerged as a candidate based on a purely text mining approach applied by a machine learning method. Polycrystalline samples of Cu 3−x Te 2 within the homogeneity range (x = 0.1, 0.2) were successfully synthesized from the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…The researchers demonstrated that such an approach, if applied in the past using historical data, may have subsequently predicted many recently reported thermoelectric materials; they also presented a list of potentially interesting thermoelectric compositions using the known literature at the time. Since then, several of these predictions have been tested either computationally [277][278][279][280][281][282] or experimentally 283 as potential thermoelectrics. Such approaches have recently been applied to search for understudied areas of metallocene catalysis 284 , although challenges still remain in such direct approaches to materials prediction.…”
Section: Software Libraries For Nlpmentioning
confidence: 99%
“…The researchers demonstrated that such an approach, if applied in the past using historical data, may have subsequently predicted many recently reported thermoelectric materials; they also presented a list of potentially interesting thermoelectric compositions using the known literature at the time. Since then, several of these predictions have been tested either computationally [277][278][279][280][281][282] or experimentally 283 as potential thermoelectrics. Such approaches have recently been applied to search for understudied areas of metallocene catalysis 284 , although challenges still remain in such direct approaches to materials prediction.…”
Section: Software Libraries For Nlpmentioning
confidence: 99%
“…The efficiency of thermoelectric generators is very much dependent on the conversion efficiency of the constituent thermoelectric (TE) compounds [25][26][27][28][29]. Therefore, the introduction of advanced thermoelectric materials is crucial in increasing the waste heatelectricity conversion rate.…”
Section: Thermoelectric Materials and Designsmentioning
confidence: 99%
“…The researchers demonstrated that such an approach, if applied in the past using historical data, may have subsequently predicted many recently reported thermoelectric materials; they also presented a list of potentially interesting thermoelectric compositions using the known literature at the time. Since then, several of these predictions have since been tested either computationally [322][323][324][325][326][327] or experimentally [328] as potential thermoelectrics. Recently, such approaches have also been applied to search for understudied areas of metallocene catalysis [329], although challenges still remain in such direct approaches to materials prediction.…”
Section: Applicationsmentioning
confidence: 99%